Social Media Marketing, Brand Image, and Purchase Decisions: The Mediating Role of Brand Awareness - Rafvilia Fiska; Oren Satipa Mulya (Analitika: Journal of Management and Finance, 2026)
Purpose: This study aims to examine the influence of social media marketing and brand image on consumer purchase decisions, with brand awareness acting as a mediating variable. Design/methodology/approach: A quantitative research approach was employed using a survey method. Data were collected from 80 consumers through a structured questionnaire using a five-point Likert scale. The sampling technique used was accidental sampling. Data analysis included validity and reliability tests as well as path analysis using SPSS to evaluate both direct and indirect relationships among variables. Findings: The results indicate that social media marketing and brand image did not show a significant influence on purchase decisions. Furthermore, brand awareness did not significantly mediate the relationship between social media marketing, brand image, and purchase decisions. These findings suggest that, in this context, the effectiveness of social media marketing and brand image in shaping consumer purchasing behavior remains limited. Research implications: The findings provide insights for retail businesses, particularly small and medium-sized cosmetic retailers, to reconsider their marketing strategies. Businesses may need to integrate alternative marketing approaches, such as experiential marketing, customer engagement strategies, and product differentiation, to enhance consumer awareness and purchasing behavior.